2014
DOI: 10.1371/journal.pone.0093550
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Like Receptor 4 Polymorphism Asp299Gly but Not Thr399Ile Influences TLR4 Signaling and Function

Abstract: The common, co-segregating Toll-like receptor 4 (TLR4) non-synonymous single nucleotide polymorphisms (SNPs), Asp299Gly and Thr399Ile, are associated with hyporesponsiveness to inhaled lipopolysaccharide (LPS) and increased susceptibility to Gram negative pathogens in humans. The purpose of this study was to identify the relative contributions of the Asp299Gly and the Thr399Ile variants in inhibiting the function of TLR4. 293/hMD2-CD14 cell line was transfected with lentiviral constructs containing human wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 39 publications
(57 reference statements)
1
27
0
1
Order By: Relevance
“…It is mainly Asp299Gly not Th r399Ile polymorphism that leads to modifi ed peptide structure, alters ligand-receptor interaction, post-receptor signaling and further cytokine production (Ferwerda et al 2008;Ohto et al 2012;Long et al 2014). TLR4 actively contributes to the infl ammatory response in development of microvascular complications, including diabetic retinopathy (Rajamani and Jialal 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly Asp299Gly not Th r399Ile polymorphism that leads to modifi ed peptide structure, alters ligand-receptor interaction, post-receptor signaling and further cytokine production (Ferwerda et al 2008;Ohto et al 2012;Long et al 2014). TLR4 actively contributes to the infl ammatory response in development of microvascular complications, including diabetic retinopathy (Rajamani and Jialal 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The above data suggested that TLR3 genetic polymorphism could be a useful and promising target for the treatment of HCC. Genetic polymorphisms have been reported to play a role in regulating transcription activities and genetic expression levels (Long et al, 2014;Shen et al, 2015). Long et al found that cells expressing TLR4 Asp299Gly polymorphism produced less IL-8 (Long et al, 2014), while Shen et al reported that TLR4 polymorphism is associated with increased susceptibility to bladder cancer possibly by downregulating gene expression in various immune cells .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms have been reported to play a role in regulating transcription activities and genetic expression levels (Long et al, 2014;Shen et al, 2015). Long et al found that cells expressing TLR4 Asp299Gly polymorphism produced less IL-8 (Long et al, 2014), while Shen et al reported that TLR4 polymorphism is associated with increased susceptibility to bladder cancer possibly by downregulating gene expression in various immune cells . Based on the above results, we speculate that the TLR3 3775290 polymorphism might contribute to HCC development by regulating the expression of TLR3 and activation in the TLR3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The TLR4 polymorphism c.896A>G has been studied and it was related to an increased susceptibility to Gram-negative bacteremia and septic shock (16,17), by reducing LPS responsiveness. This hypo- responsiveness to LPS associated with the c.896A>G polymorphism is not due to a reduced surface TLR4 protein expression; instead, the polymorphism must alter the ability of TLR4 to interact with myeloid differentiation factor 2 (MD-2), with LPS and/or by inducing signal eliciting (18). Crystal structure of the tertiary TLR4/MD-2/LPS complex was recently elucidated for both wild-type and mutant TLR4 (19).…”
Section: Discussionmentioning
confidence: 99%